Pengelolaan Kelas dalam Meningkatkan Motivasi Belajar Siswa di SD Negeri Dawung, Tegalrejo, Magelang, Jawa Tengah - Sulastri, Sulastri (Prosiding University Research Colloquium, 2021)
This study was used to determine the real situation of classroom management at SD Negeri Dawung, Tegalrejo, Magelang. The method used by the author in this study is a qualitative method. Data collection techniques aree interviewers, observation and documentation. Includes classroom management in the form of physical, including classrooms, table and chair arrangements, furniture and other learning tools and non physical related to students. Therefore educators have the main responsibility in schools, teachers are directly involved in learning activities at the school, teachers have the task of shaping the character of students in schools, helping students develop their talents and interests, and improving the quality of education in order to increase students motivation. Creative skilla in learning activities during teaching and learning activities take place one way is by classroom management.